Inovasi Sarana Pengurusan Dokumen Berbasis Elektronik Di Kantor Kelurahan Buliang, Batu Aji - Eko Prastius; Fedric Fedric; Jessica Jessica; Puteri Ariesta Nadia; Rachmawan Rachmawan; Velany Kosasih (National Conference for Community Service Project (NaCosPro), 2019)
In Batam International University, there has a program which is known as SEPORA (Society Empowerment Program). In this program each team of Student has to create an innovation about Community services in a certain area which has been determined by lecturer. Our mission is to provide the fastest way for citizens of Buliang to create their important documents such as ID Card, Family Card ,Business domicile and other important documents. We started this project by creating a website with the database that connected to each others so the citizens of Buliang can sign up for online queue, so they didn’t have to go to Buliang district office to handle it, they can sign up by fill up the form in the website that we provided and the information will be recorded into Buliang’s database system. We also taught several citizens of Buliang how to access the website and sign up the queue form from their own phone. We hope that our little project here can help to boost Buliang's government performance and can help the citizen of Buliang so they didn’t have to wait to submit their form.